Enhancing non-cognitive skills by applying lesson study in lower secondary education: A project in Vietnam - Seonkyung Choi; Tatsuya Kusakabe; Yoshiyuki Tanaka (Cogent Education, 2022)
This study examined the quantitative relationship between lesson study and non-cognitive skills in Vietnam, using t-test analysis for comparison before and after. We also looked at the relationship between lesson study and cognitive skills, teacher engagement and parental involvement. Unlike former studies, we found no relationship between lesson study and cognitive skills, however that is consistent with the general finding in the literature that lesson study seems to have more of an impact on academic performance at the primary than at the secondary level. Nonetheless, and most importantly, we did find a statistically significant relationship between lesson study and non-cognitive skills, specifically extraversion and conscientiousness, two of the Big Five traits that psychologists generally agree make up the taxonomy of non-cognitive traits. We also found that lesson study led teachers to have more dialogue with their students and parents to engage more with their children on their academic progress. In light of the correlation between lower secondary education and non-cognitive skills, these results suggest that lesson study at the lower secondary level may lead to improved academic outcomes at the upper secondary and higher education levels as well as improved life outcomes including behavioral and labor market outcomes.